Hexokinase-linked glycolytic overload and unscheduled glycolysis in hyperglycemia-induced pathogenesis of insulin resistance, beta-cell glucotoxicity, and diabetic vascular complications - Rabbani, Naila; Thornalley, Paul J. (Frontiers in Endocrinology, 2024)
Hyperglycemia is a risk factor for the development of insulin resistance, beta-cell glucotoxicity and vascular complications of diabetes. We propose the hypothesis, Hexokinase-linked glycolytic overload and unscheduled glycolysis, in explanation. Hexokinases (HKs) catalyze the first step of glucose metabolism. Increased flux of glucose metabolism through glycolysis gated by HKs, when occurring without concomitant increased activity of glycolytic enzymes -unscheduled glycolysis, produces increased levels of glycolytic intermediates with overspill into effector pathways of cell dysfunction and pathogenesis. HK1 is saturated with glucose in euglycemia and, where the major HK, provides for basal glycolytic flux without glycolytic overload. HK2 has similar saturation characteristics except, in persistent hyperglycemia, it is stabilized to proteolysis by high intracellular glucose concentration -increasing HK activity and initiating glycolytic overload and unscheduled glycolysis. This drives the development of vascular complications of diabetes. Similar HK2-linked unscheduled glycolysis in skeletal muscle and adipose tissue in impaired fasting glucose drives the development of peripheral insulin resistance. Glucokinase (GCK or HK4) linked glycolytic overload and unscheduled glycolysis occurs in persistent hyperglycemia in the hepatocytes and beta-cells, contributing to hepatic insulin resistance and beta-cell glucotoxicity leading to the development of type 2 diabetes. Downstream effector pathways of HK-linked unscheduled glycolysis are: mitochondrial dysfunction and increased reactive oxygen species (ROS) formation, activation of hexosamine, protein kinase c and dicarbonyl stress pathways, and increased Mlx/Mondo A signaling. Mitochondrial dysfunction and increased ROS was proposed as the initiator of metabolic dysfunction in hyperglycemia but it is rather one of multiple downstream effector pathways. Correction of HK2 dysregulation is proposed as a novel therapeutic target. Pharmacotherapy addressing it corrected insulin resistance in overweight and obese subjects in clinical trial. Overall, the damaging effects of hyperglycemia are a consequence of HKgated increased flux of glucose metabolism without increased glycolytic enzyme activities to accommodate it.